A descriptive study of role of corporate citizen in sustainable development through green finance framework - Yadav, Pankaj (Journal of Social Review and Development, 2022)
With the robust concern of preservation of environment and atmospheric change there is a requirement of the classic way that helps in reducing the carbon emissions. The unreliable extraction of natural resources due to man-made activities is the sole reason of environmental damage. This reason leads to the alarming interrelation between human kind and earth. It presents a room to maneuver to corporate citizens to reassess the ‘Business-as-usual’ and orient it with SDGs although the gap is unfulfilled with the current scenario. Businesses are often considered as the engine of the economy and adding up the sustainability to the businesses may help in stepping towards carbon neutrality. The huge amount of funding is required for the sector for renewable development so there is urgent need of requirement of different sources of financing that may help in achievement of SDGs. Besides the different ways of sourcing of finance, it also needs a way of channelizing these funds in the economy with the alignment of earth friendly manner.